Characterization of a bioactive polysaccharide from Ganoderma atrum: Re-elucidation of the fine structure. (20th February 2017) - Zhang, Hui; Nie, Shaoping; Cui, Steve W.; Xu, Ming; Ding, Huihuang; Xie, Mingyong
Highlights: PSG-1 was re-purified and the structure was re-elucidated with more evidences. β-(1 → 3)-glucan was identified as the backbone with branch point at O -6 of glucose. Long β-(1 → 6)-glucose side chain was proposed. β-(1 → 4)-GlcA was found in the side chain of PSG-1. Abstract: The fine structure in terms of backbone and branch chain features of a bioactive polysaccharide from Ganoderma atrum (PSG-1) was re-elucidated systematically using high performance anion-exchange chromatography (HPAEC), methylation and GLC–MS analysis, and 1D & 2D NMR spectroscopy. Monosaccharide composition analysis revealed that PSG-1-F0.2 fraction mainly consisted of glucose (73.8%) and glucuronic acid (15.3%), with small amount of mannose (5.7%) and galactose (5.2%). Based on methylation, multistep partial acid hydrolysis and NMR study, were proposed to substitute at the O -6 position of β-(1 → 3)-glucan. The small amount of mannose and galactose residues were considered to be from the other fraction in PSG which was very difficult to be separated from PSG-1-F0.2 . This revised structure as an acidic β-(1 → 3, 1 → 6)-glucan is considered to be more accurate than the previous proposal of PSG-1.